Credit Unions: Theory, Empirical Evidence and Public Regulation: Discussion - Flannery, Mark J. (Journal of Finance, 1981)
Mark J. Flannery, Credit Unions: Theory, Empirical Evidence and Public Regulation: Discussion, The Journal of Finance, Vol. 36, No. 2, Papers and Proceedings of the Thirty Ninth Annual Meeting American Finance Association, Denver, September 5-7, 1980 (May, 1981), pp. 554-556